Coffee‐ring‐effect‐induced water scale formation of silicic acid‐containing droplet. Issue 5 (30th July 2020) - Hayashi, Shogo; Kobayashi, Tomoki; Saito, Noritaka; Nakashima, Kunihiko
Abstract: The drying behavior of silicic acid‐containing water droplets on a glass substrate was investigated by using as‐prepared aqueous silica solutions of varying concentrations to simulate water scale‐like formation. The droplets of aqueous silica solution were found to form circumferential solid silica deposits (water scale). Additionally, the drying behavior of the silica droplets was observed under varying temperature and humidity. Optical microscopy images of the deposited material showed thicker deposits in the inner part of the circumference, indicating the so‐called rush‐hour effect and induced by the coffee‐ring effect. Thus, the formation of water scale observed in daily life can be attributed to the coffee‐ring effect. Scanning electron microscopy confirmed that the as‐prepared water scale consisted of polymerized silica spheres. The hardness of the water scale depended on the amount of silica deposited and the initial concentration of the silica solution. Thus, the formation of water scale in daily life was concluded to occur by two mechanisms: formation of silica spheres by silica polymerization and agglomeration‐deposition by the coffee‐ring effect. Abstract : In this study, we formed an artificial water scale by using droplets of silica‐containing water. The artificial water scale formation occurred through the coffee ring effect. The water scale was produced from innumerable silica particles, which agglomerated to form a bulk of silica scale.